(untitled) (Romano-arabica, 2025)
What should be the goal of teaching grammar in the language learning process? What is the best method to adopt in the specific case of the Arabic language, which has its own millennial tradition of grammatical studies? Can the use of this tradition, which has developed a peculiar conceptual framework and its own perspective of analysis, be helpful to teachers and students who have been formed within the Western linguistic tradition? Might the pitfalls hidden in juxtaposing two different traditions of study exceed the advantages and thus undermine the efforts? An attempt to answer these questions will be made in this article, but only after providing a brief definition of the concept of grammatical tradition and mentioning the changes undergone by the term naḥw as for its semantic field and scope. A careful consideration of the complex problem of the terminological correspondence and the translatability of Arabic terminology will, therefore, allow us to lay the terms of the issue. Finally, the thesis that, faced with approximate interpretations and unconvincing explanations given by Arabists, the recourse to the tradition of Arab grammarians can be helpful, provided it is motivated, oriented, and reasonably limited, will be argued through the discussion of two fundamental grammatical topics: on the one hand, the function of the mubtadaʾ as it is described in a previous article by Michele Vallaro (1948-2023); on the other hand, the alleged opposition between māḍī and muḍāriʿ, in which the Arabic verbal system would be grounded, compared with what is stated by ʾAbū al-Qāsim al-Suhaylī (d. 1185) in his Natāʾiǧ al-fikr fī al-naḥw.